An Appraisal of Drug-Drug Interactions with Green Tea (Camellia sinensis) - Albassam, Ahmed A.; Markowitz, John S. (Planta Medica, 2017)
This review summarizes published in vitro, animal, and clinical studies investigating the effects of green tea (Camellia sinensis) extract and associated catechins on drug-metabolizing enzymes and drug transporters. In vitro studies suggest that green tea extract and its main catechin, (−)-epigallocatechin-3-gallate, to varying degrees, inhibit the activity of CYP1A1, CYP1A2, CYP2B6, CYP2C8, CYP2C9, CYP2D6, and CYP3A4. UGT1A1 and UGT1A4 isoforms were also inhibited by (−)-epigallocatechin-3-gallate. Animal studies suggest green tea extract and/or (−)-epigallocatechin-3-gallate significantly increase the bioavailability of diltazem, verapamil, tamoxifen simvastatin, 5-fluorouracil, and nicardipine. Conversely, green tea extract and/or (−)-epigallocatechin-3-gallate reduce the bioavailability of quetiapine, sunitinib, clozapine, and nadolol. Of the few clinical studies available for review, it appears neither green tea extract nor (−)-epigallocatechin-3-gallate inhibit any major cytochrome P450 enzyme. Regarding drug transporters, in vitro studies indicate P-glycoprotein, organic anion transporting polypeptide 1A1, organic anion transporting polypeptide 1B1, organic anion transporting polypeptide 1B3, organic anion transporting polypeptide 2B1, organic cation transporter 1, organic cation transporter 2, multidrug and toxin extrusion 1, and multidrug and toxin extrusion 2-K are potentially inhibited by green tea extract. A clinical study indicates the organic anion transporting polypeptide 1A1 transporter is inhibited by (−)-epigallocatechin-3-gallate while P-glycoprotein is unaffected. In conclusion, the ingestion of green tea extract or its associated catechins is not expected to result in clinically significant influences on major cytochrome P450 or uridine 5′-diphospho-glucuronosyltransferase enzyme substrates or drugs serving as substrates of P-glycoprotein. However, some caution is advised in the consumption of significant amounts of green tea beverages or green tea extract in patients prescribed known substrates of organic anion transporting polypeptide, particularly those with a narrow therapeutic index.
Keywords: green tea; Camellia sinensis; Theaceae; epigallocatechin gallate; cytochrome P450; uridine 5′-diphospho-glucuronosyltransferase; transporter; herb-drug interaction